IPTEKS SISTEM PENGENDALIAN INTERN PEMERINTAH PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI SULAWESI UTARA - Soeda, Endri Brifio; Rondonuwu, Sintje (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
This research is intended to find out the appropriate or not yet the application of the System of Internal Control of the Government in the Department of Industri and Trade of the North Sulawesi Province with Government Regulation No. 60 Year 2008 about Control Systems Government Intern, by way of identifying what became an obstacle in the process of implementation of the SPIP and any efforts being undertaken in dealing with the application of constraints of SPIP for increased levels of maturity of SPIP. The general the application of SPIP in Department of industry and trade of the North Sulawesi province were in accordance with government regulation No. 60 the year 2008 about SPIP. But, not to the achievement of the target level of 3 (three) maturity of SPIP in the Departmen of industry and trade shows that the application of SPIP still experience particular constraints. As for the constraints in the implementation of SPIP namely; 1) HR which is not yet competent, 2) lack of discipline, 3) evaluation activities, inadequate. Efforts are being made to overcome the constraints in the implementation of SPIP are: 1 HR development programÂ  through training of his own Office, 2) build effective communication, 3) build organizational commitment.Keywords: The System of Internal Control of the Government, The Level of Maturity of the Organization of the SPIP, Constraints and Efforts.